Literature Review: Nutritional Therapy for Patients in the Intensive Care Unit (ICU) - Andi Zakiyah Aulia Salsabila Ashar (Journal of Nutrition and Health Care, 2024)
Nutritional therapy is an important component in the care of critical patients in the Intensive Care Unit (ICU). This literature review aims to analyze the current evidence regarding optimal nutritional therapy strategies for ICU patients. A systematic search was conducted in the PubMed, Cochrane Library, and EMBASE databases for studies published within the last 10 years. A total of 45 articles meeting the inclusion criteria were analyzed, including randomized clinical trials, meta-analyses, and clinical practice guidelines. The results of the review show that early initiation of enteral nutrition (within 24-48 hours after admission) is associated with reduced mortality and infectious complications compared with delayed nutrition. However, aggressive enteral nutrition should be avoided due to the risk of gastrointestinal intolerance. Parenteral nutrition should be considered if enteral nutrition is inadequate after 7-10 days. Close monitoring of nutritional status and adjustment of calorie-protein intake based on disease phase is essential. Supplementation of immunonutrients such as glutamine, arginine, and omega-3 fatty acids shows potential benefits in certain patient subgroups, but the evidence remains controversial. Routine administration of vitamins and trace elements is not recommended unless specific deficiencies are present. Tight glycemic control (80-110 mg/dL) is no longer recommended due to the increased risk of hypoglycemia, with looser targets (140-180 mg/dL) considered safer. In conclusion, an individualized and dynamic nutritional therapy approach is needed for ICU patients. Early enteral nutrition remains the modality of choice, with parenteral nutrition as a complement if needed. Close monitoring and adjustment of therapy based on tolerance and phase of disease is essential. Further research is needed to optimize nutritional strategies in diverse ICU patient populations.